THE EFFECT OF PLANTING DATE ON THE YIELD AND VEGETATIVE GROWTH CHARACTERS OF THE STRAWBERRY IN SULAYMANI REGION - Hamarash, Abdul Mostafa; Hassan, Ismail Ahmed; Ahmed, Mahmud Karim (Diyala Agricultural Sciences Journal, 2015)
This research was implemented in the fields of Bakrajo Technical Agricultural Institute /Sulaymani governorate during winter season 2011/2012 . Hapil cultivar of strawberry which is well known in the area used in this research with six planting dates ,with 15 days interval , starting from Dec.10/2011 until Feb.25/2012 respectively in addition to control treatment (planting in the nursery). RCBD was used in three replications .Each plot involved 20 plants , data were recorded from five plants randomly for each experimental units. Data analysis and LSD test at %5 level were achieved . The results showed after the fruits ripening and that have been harvested starting from April 282012 And with fifteen picking until May 30-2012,that the planting date Dec.10-2011 and Feb.10 -2012 gave earlier and more fruits compared with the others . The mean number of leaves were 24.22 and 21.5 leaves/plant during Feb.10-2012 and Jan.15-2012 respectively. The mean number of flowers were 8.33 and 6.63 flowers/plant during Feb.10-2012 and Dec.10-2011 plant dates respectively. The mean number of lateral shots were higher in the three planting times Feb.25,10,2012 and Jan.102012 with mean 4.80,4.87 and 4.90 shots/plant . The mean number were 6.84 and 6.6 during Feb.10-2012 and Jan. 25-2012 respectively ,The mean length of leaf petioles were 11.43 and 10.10 centimetres during Dec.10-2011 and Feb.102012 planting dates respectively.